The Problems of Developing the Ecological Market of the Region; Applied Mechanics and Materials; Vol. 682 : Innovation Technology and Economics in Engineering - Shabashev V. A. Vladimir Alekseevich (Management and Economic Aspects Development of Enterprises, 2014)
Title screen